Incremental exercise test for the evaluation of peak oxygen consumption in paralympic swimmers - Sa Souza, Helton de; Alves, Eduardo Da Silva; Ortega, Luciana; Silva, Andressa; Esteves, Andrea Maculano; Schwingel, Paulo Adriano; Vital, Roberto; Da Rocha, Edilson Alves; Rodrigues, Bruno; Lira, Fabio Santos [UNESP]; Tufik, Sergio; De Mello, Marco Tulio (Edizioni Minerva Medica, 2016)
BACKGROUND: Peak oxygen consumption (VO(2)peak) is a fundamental parameter used to evaluate physical capacity. The objective of this study was to explore two types of incremental exercise tests used to determine VO(2)peak in four Paralympic swimmers: arm ergometer testing in the laboratory and testing in the swimming pool. METHODS: On two different days, the VO(2)peak values of the four athletes were measured in a swimming pool and by a cycle ergometer. The protocols identified the VO(2)peak by progressive loading until the volitional exhaustion maximum was reached. The results were analyzed using the paired Student's t-test, Cohen's d effect sizes and a linear regression. RESULTS: The results showed that the VO(2)peak values obtained using the swimming pool protocol were higher (P=0.02) than those obtained by the arm ergometer (45.8 +/- 19.2 vs. 30.4 +/- 15.5; P=0.02), with a large effect size (d=3.20). When analyzing swimmers 1, 2, 3 and 4 individually, differences of 22.4%, 33.8%, 60.1% and 27.1% were observed, respectively. CONCLUSIONS: Field tests similar to the competitive setting are a more accurate way to determine the aerobic capacity of Paralympic swimmers. This approach provides more sensitive data that enable better direction of training, consequently facilitating improved performance.
Keywords: Exercise test; Sports for Persons with disabilities; Disabled Persons; Atheletes